A new approximation method for common fixed points of a finite family of asymptotically quasi-nonexpansive mappings in Banach spaces - Atichart Kettapun (2018)
In this paper, we consider a new iterative scheme to approximate a common fixed point for a finite family of asymptotically quasi-nonexpansive mappings. We prove several strong and weak convergence results of the proposed iteration in Banach spaces. These results generalize and refine many known results in the current literature. © 2010 Elsevier Ltd. All rights reserved.